2021
DOI: 10.1177/17470218211043434
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of occasional reinforced extinction to alleviate spontaneous recovery and reinstatement effects: Evidence for a trial-signalling mechanism

Abstract: Fear extinction is not permanent but is instead more vulnerable than the original fear memory, as traditionally shown by the return of fear phenomena. Because of this, techniques to mitigate the return of fear are needed in the clinical treatment of related psychological conditions. One promising strategy is the occasional reinforced extinction treatment, introducing a gradual and sparse number of CS-US pairings within the extinction treatment. We present the results of three experiments in which we used a thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…For instance, although both Culver et al (2018) and Thompson et al (2018) found evidence of a reduced spontaneous recovery, the former did so on SCR and expectancy ratings, whereas the latter only found a benefit on SCR. 4 Regarding reacquisition, Culver et al (2018) could only find an effect on the SCR measure, at odds with other studies (see Morís et al, 2017;Quintero et al, 2022;van den Akker et al, 2015), where the rate of reacquisition was slowed down when measured as expectancy ratings.…”
Section: Primary Outcome Measuresmentioning
confidence: 75%
See 3 more Smart Citations
“…For instance, although both Culver et al (2018) and Thompson et al (2018) found evidence of a reduced spontaneous recovery, the former did so on SCR and expectancy ratings, whereas the latter only found a benefit on SCR. 4 Regarding reacquisition, Culver et al (2018) could only find an effect on the SCR measure, at odds with other studies (see Morís et al, 2017;Quintero et al, 2022;van den Akker et al, 2015), where the rate of reacquisition was slowed down when measured as expectancy ratings.…”
Section: Primary Outcome Measuresmentioning
confidence: 75%
“…The results of an occasional reinforced intervention on the reacquisition of the conditioned response tend to be the most consistent, with six out of eight experiments finding a significant effect, both in animals and in humans, and using either appetitive or aversive procedures. Results regarding other relapse phenomena tend to be less reliable, with some tests showing beneficial effects of ORE on the prevention or reduction of spontaneous recovery (Gershman et al, 2013;Thompson et al, 2018) or reinstatement (Gershman et al, 2013;Shiban et al, 2015), while others did not (see Quintero et al, 2022, andThompson et al, 2018). Finally, only one article has studied renewal after ORE, finding no significant results (Lipp et al, 2021).…”
Section: Summary Of the Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exclusion criteria. As in Morís et al (2017; Experiment 3) and Quintero et al (2022), we used some rejection criteria to exclude from further analyses data from participants who had a poor understanding of the contingencies programmed. In those two previous studies, the criteria were based on the distribution of data obtained for each group, removing participants that deviated more than two standard deviations in several measures.…”
Section: Data-analysesmentioning
confidence: 99%